Control of Ocean Temperature on Jakobshavn Isbræ's Present and Future Mass Loss - Johannes H. Bondzio; Mathieu Morlighem; Hélène Seroussi; Michael H. Wood; Jérémie Mouginot (Geophysical Research Letters)
Abstract Large uncertainties in model parameterizations and input data sets make projections of future sea level rise contributions of outlet glaciers challenging. Here we introduce a novel technique for weighing large ensemble model simulations that uses information of key observables. The approach is robust to input errors and yields calibrated means and error estimates of a glacier's mass balance. We apply the technique to Jakobshavn Isbræ, using a model that includes a dynamic calving law, and closely reproduce the observed behavior from 1985 to 2018 by forcing the model with ocean temperatures only. Our calibrated projection suggests that the glacier will continue to retreat and contribute about 5.1 mm to eustatic sea level rise by 2100 under present‐day climatic forcing. Our analysis shows that the glacier's future evolution will strongly depend on the ambient oceanic setting.